Biopolymer from the Puree of Mesocarp of Citrullus lanatus (Watermelon) Containing Chlorhexidine Digluconate: Physical-Chemistry Characterization and Biological Aspects - Paris Junior, José Alberto; Nogueira, Leonardo Gorla; Cerqueira, Igor Henrique; Catirse, Nicole Pichirilli; da Silva, Lucas Henrique Domingos; de Abreu Fernandes, Paula; Colturato, Vitória Maria Medalha; dos Santos Dias, Diógenes [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Dametto, Alessandra Cristina; Silva, Jhonatan Miguel; da Silva Barud, Hernane; et al. (Springer Nature, 2024)
Fruit and vegetable waste is a promising source to produce functional polymeric films, given the urgent need to replace petroleum-based polymeric materials due to their environmental impacts and limited sustainability. In the present study, we produced an antimicrobial surface film derived from watermelon mesocarp containing chlorhexidine in digluconate form (W-CHX) with applicability for coating 2D surfaces and medical devices. The films were obtained by hydrothermal steps and casting, and characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, thermal stability profile, water barrier properties, fluid handling ability, and drug release, in addition to the assessment of antibacterial, cytotoxic, and mutagenic potential. Although the W-CHC films have demonstrated promising mechanical and antibacterial properties against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli, their cytotoxicity and genotoxicity in keratinocytes (HaCaT cells) as revealed by the Comet assay highlight the need for cautious use for topical applications. Therefore, the attributes exhibited by W-CHX films offer a pathway to address the escalating need for biopolymer-based materials with enhanced performance, particularly in extracorporeal applications necessitating microbial growth inhibition. Graphical Abstract: Antimicrobial surface film: watermelon mesocarp-only biopolymers with chlorhexidine (CHX) (Figure presented.)
Keywords: Antimicrobial surface film; Biopolymer-based materials; Cytotoxic; Genotoxicity; Watermelon mesocarp